Targeting poverty through community-based public works programs: A cross-disciplinary assessment of recent experience in South Africa - Adato, Michelle; Haddad, Lawrence J. (International Food Policy Research Institute, 2001)
Since the transition to democracy, South African public works programs are to involve community participation, and be targeted to the poor and women. This paper examines the targeting performance of seven programs in Western Cape Province, and analyzes the role of government, community-based organizations, trade unions, and the private sector in explaining targeting outcomes. These programs were not well-targeted geographically in terms of poverty, unemployment, or infrastructure. Within localities, jobs went to the poor and unemployed, though not always the poorest. They did well in reaching women, despite local gender bias. Targeting guidelines of the state are mediated by diverse priorities that emerge in programs with multiple objectives, local perceptions of need and entitlement, and competing voices within civil society.